Use of an electronic Partograph: feasibility and acceptability study in Zanzibar, Tanzania - Lindsay Elizabeth Litwin; Christina Maly; Asma Ramadan Khamis; Cyndi Hiner; Jérémie Zoungrana; Khadija Mohamed; Mary Drake; Michael Machaku; Mustafa Njozi; Salhiya Ali Muhsin; Yusuph K. Kulindwa; Patricia P. Gomez (BMC, 2018)
Abstract Background The ePartogram is a tablet-based application developed to improve care for women in labor by addressing documented challenges in partograph use. The application is designed to provide real-time decision support, improve data entry, and increase access to information for appropriate labor management. This study's primary objective was to evaluate the feasibility and acceptability of ePartogram use in resource-constrained clinical settings. Methods The ePartogram was introduced at three facilities in Zanzibar, Tanzania. Following 3 days of training, skilled birth attendants (SBAs) were observed for 2 weeks using the ePartogram to monitor laboring women. During each observed shift, data collectors used a structured observation form to document SBA comfort, confidence, and ability to use the ePartogram. Results were analyzed by shift. Short interviews, conducted with SBAs (n = 82) after each of their first five ePartogram-monitored labors, detected differences over time. After the observation period, in-depth interviews were conducted (n = 15). A thematic analysis of interview transcripts was completed. Results Observations of 23 SBAs using the ePartogram to monitor 103 women over 84 shifts showed that the majority of SBAs (87-91%) completed each of four fundamental ePartogram tasks-registering a client, entering first and subsequent measurements, and navigating between screens-with ease or increasing ease on their first shift; this increased to 100% by the fifth shift. Nearly all SBAs (93%) demonstrated confidence and all SBAs demonstrated comfort in using the ePartogram by the fifth shift. SBAs expressed positive impressions of the ePartogram and found it efficient and easy to use, beginning with first client use. SBAs noted the helpfulness of auditory reminders (indicating that measurements were due) and visual alerts (signaling abnormal measurements). SBAs expressed confidence in their ability to interpret and act on these reminders and alerts. Conclusions It is feasible and acceptable for SBAs to use the ePartogram to support labor management and care. With structured training and support during initial use, SBAs quickly became competent and confident in ePartogram use. Qualitative findings revealed that SBAs felt the ePartogram improved timeliness of care and supported decision-making. These findings point to the ePartogram's potential to improve quality of care in resource-constrained labor and delivery settings.